Using Alternative Raw Materials in Sugar Confectionery Production - Hovhannisyan, N. G.; Mkhitaryan, H. V.; Aperyan, G. B.; Hayrapetyan, R. S. (ՀԱԱՀ հիմնադրամ)
A novel recipe and production technology for sugar confectionery, specifically marmalade, has been developed through scientific and experimental research. The findings affirm that pumpkin and sea buckthorn purees can effectively substitute traditional plum and apple purees, eliminating the need for various coloring agents. The suggested product represents a domestically-produced marmalade, particularly in the food market, and this endeavor will play a crucial role in advancing both marmalade production and the development of the raw material base.
Keywords: Food Science and Technology